ESTIMATING THE ECONOMIC VALUE OF THE ECOTOURISM DESTINATION: THE CASE OF TRA SU MELALEUCA FOREST NATURAL PARK IN VIET NAM - Truong Huy, Huynh; Thi Ngoc Thi, Luu; Tri Nam Khang, Nguyen; Thi Tu Trinh, Nguyen (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2023)
In this article, the application of the Individual Travel Cost Method (ITCM) aims at providing a deeper insight into visitors’ preferences and their expenses on marketed and non-marketed services when travelling to the Tra Su Melaleuca Forest Natural Park, an ecotourism destination in An Giang Province of Viet Nam. The empirical findings from the survey of 237 visitors in 2022 showed that the frequency of trips to this recreational site was 1.3 per year on average and relied strongly on the travel costs. Additionally, the estimate of tourism revenues for 2022 of this site was 82,3 billion Viet Nam Dong (VND; equivalent to 3,5 million USD). Meanwhile, its economic value calculated by the ITCM application reaches 206,2 billion VND (or 8,8 million USD). It is obvious that a greater economic value over the monetary amount of revenue also raises several ideas of managerial implications dedicated to the recreational site. It includes building a marketing team for developing recreational services and digital marketing performance, expanding tour services like transportation, lodging, local guides. Finally, enabling local people to engage in dialogues, decision-making, and interest shares is also necessary for the sustainable development of ecotourism.